Catalytic Aromatization of Propane-Butane Fraction - N.I.Fayzullaev, S.Yu. Bobomurodova (International Journal of Advanced Science and Technology, 2020)
In this research work, the propane-butane fractions are aromatized catalytically for the reaction of obtaining aromatic hydrocarbons and liquid fuels. Various types of catalytic catalysts for the productivity of reaction were also studied.The experiments were carried out in a flow catalytic device in the stationary phase of the catalyst (catalyst volume 6 cm3), at 450-600ºC, at normal atmospheric pressure (P = 0.1 MPa), under volumetric rate of propane-butane fraction 400-600 h-1.  As the result of the experiment, the best modifying additives were found Zn, Zr, Ga, and Mo. The conversion of propane begins at 450ºC and reaches 100%; where the total conversion of propane reaches 600ºC.  Aromatic hydrocarbons are formed in sufficient quantities at 500ºC and a maximum value of 52.5% is reached at 600ºC.  The conversion of butane to aromatic hydrocarbons is easier than propane.At 550ºC the yield of aromatic hydrocarbons is 47% while the conversion of butane is 100%.  The textural and physicochemical characteristics of the catalysts were also studied in the study.Keywords: Aromatic hydrocarbons, aromatized catalytically, productivity of reaction, volumetric rate, propane-butane fraction.